Perspectives on Regional Unemployment in Europe - Spilimbergo, Antonio (Occasional Papers; Occasional Paper, 1999)
The third stage of European Economic and Monetary Union (EMU) was implemented in January 1999 against the specter of persistently high unemployment in many of the participating countries. While the high European unemployment has received considerable attention, this new IMF staff study analyzes an equally important issue: the extent of regional unemployment disparities in certain countries. The paper focuses on large and persistent differences in regional unemployment rates within several European countries. The paper includes detailed case studies of two euro area countries where regional disparities in unemployment are striking- Italy and Spain. The studies emphasize that wages are unresponsive to local labor market conditions.